Korelasi Antara IRMS dan BMS di Ruas Jalan Nasional Profinsi lampung (Studi Kasus Evaluasi Pertahun Anggaran Dari Tahun 2012 Sampai Tahun 2015) - Alawiya, Tuti; Hadi, Yohanes Martono; Adha, Idharmahadi (Universitas Lampung, 2016)
National Roads System in Lampung is the Sumatra gateway from Java to the others Provinces in Sumatra island and vice versa, and the highway as the main of development in a region that should comply the needs of the movement of traffic, among others, Fast, Convenient, Safe, Durable, and environmentally friendly. Evaluation or study was conducted to carry out the review section of the Roads System and National Bridge in Lampung based on IRMS and BMS data that is a management tool to see the condition of roads and bridge. Not affiliated between IRMS and BMS have caused the lack of evaluation on the construction and maintenance of roads and bridges on national roads in Lampung.This study aims to correlation between IRMS and BMS that the condition of roads and bridges are related, so that to taking the decision to determine the construction, periodic maintenance or routine maintenance of roads and bridges in Lampung appropriate to the real conditions by prioritizing the bridge specially the periodic maintenance.So that it can be taken a linkage that the time periode for the traffic to move from a place to the other placse is affected by the conditons of the roads and bridge. Nowadays, the result of IRMS and BMS as a benchmark that used by policy makers as a basis for determining future programs like Planning, Maintenance, and Development. While in taking decisions isn’t appropriate with the real conditions. Keywords: Correlation Between IRMS-BMS, Road and Bridge Conditions